Pengaruh Senam Kaki Terhadap Nilai ABI Pada Pasien Diabetes Mellitus : Pengaruh Senam Kaki Terhadap Nilai ABI Pada Pasien Diabetes Mellitus - Heru Wiratmoko; Endang Purwaningsih; Agus Wiwit Suwanto (Jurnal Keperawatan Terapan, 2026)
Abstract:  Diabetes Mellitus (DM) is a non-communicable disease that attracts a lot of attention. Severe arterial occlusive disease in the lower extremities in the form of peripheral artery disease (PAD). Type 2 DM sufferers are at two to three times the risk of developing peripheral arterial occlusive disease compared to non-DM sufferers (Jonathan, 2019). One way to detect PAD early can be done by examining the circulation by calculating the Ankle Brachial Index (ABI) value. It is hoped that foot exercises will improve circulation in the peripheral blood vessels in the legs. The aim of the study was to determine the effect of foot exercise intervention on ABI values ??in diabetes mellitus patients. The research method is true experimentation. The research population was diabetes mellitus sufferers in Kutu Wetan village, Kec. Jetis numbered 67 people, the research sample was a purpusive sample of 40 people. Data were collected by examining ABI values ??before and after the DM foot exercise intervention..The results of the Paired T Test obtained values ??(p value = right leg 0.005 and left leg 0.023 ? 0.05) indicating that there is a significant relationship between DM Foot Exercises and ABI Values ??in DM Sufferers. Keyword: DM Foot Exercises, ABI value, Diabetes Mellitus Patients